1993
DOI: 10.1002/ca.980060305
|View full text |Cite
|
Sign up to set email alerts
|

Age changes in the human laryngeal cartilages

Abstract: Various changes in the human laryngeal cartilages have been studied by the naked eye, radiology, and histology in 28 dissecting room and 20 autopsy specimens (21 male and 27 female) ranging from 14 to 101 years. Except for one 14-and one 20-year-old specimen, radiographic signs of calcification occurred in all and were found in hyaline cartilaginous tissue of the thyroid, cricoid, arytenoid, and the variably occurring triticiate cartilages. A series of stages has been established indicating the pattern of spre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
42
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 6 publications
8
42
0
Order By: Relevance
“…10,11 This is in concordance with the hypothesis that the order of ossification is affected by the distribution of mechanical forces applied to the laryngeal cartilages, 8 because the lateral and posterior cricoarytenoid muscles attach to the lateral part (muscular process) of the arytenoid.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…10,11 This is in concordance with the hypothesis that the order of ossification is affected by the distribution of mechanical forces applied to the laryngeal cartilages, 8 because the lateral and posterior cricoarytenoid muscles attach to the lateral part (muscular process) of the arytenoid.…”
Section: Discussionsupporting
confidence: 85%
“…5,6 Hyaline cartilages undergo changes with time, with progressive enchondral ossification. 7,8 Histopathologic studies demonstrated that the stage of the calcification and ossification is widely affected by age. 9 The order of ossification is affected by the distribution of the mechanical forces applied to the laryngeal cartilages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Calcium deposition can occur with aging and various pathologic processes [1] with cartilaginous ossification or calcification often found in the elderly, including bronchial cartilage [2], laryngeal cartilage [3], and various articular cartilages [4].…”
Section: Dear Sirmentioning
confidence: 99%
“…Ossification of the cricoid cartilage starts about the age of 20 years in men and 22 years in women and is first observed in the region of the cricoarytenoid joint (Chievitz, 1883;von Lanz and Wachsmuth, 1955) and the superior border of the lamina (Turk and Hogg, 1993). Ossification then spreads along the entire superior rim of the arch and involves the cranial portions of the cartilage.…”
Section: Posterior Bordermentioning
confidence: 99%